2009
DOI: 10.1051/ocl.2009.0279
|View full text |Cite
|
Sign up to set email alerts
|

Oils of insects and larvae consumed in Africa: potential sources of polyunsaturated fatty acids

Abstract: The objective of this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 17 publications
3
62
1
1
Order By: Relevance
“…There is a high variation in fatty acids profiles across insect species (Thompson, 1973;Lu et al, 1992). Womeni et al (2009) reported fatty acids of several edible insect species consumed in Cameroon to contain quantities of palmitic (8-38 %), oleic (9-48 %), linoleic (7-46 %) and α-linolenic acid (15-38 %) as percentage of oil content. Although the nutritional importance of linoleic and α-linolenic acid as essential amino acids is well recognized, the presence of high amounts of unsaturated fatty acids will also give rise to rapid oxidation of insect food products during processing, causing them to go rancid quickly (FAO, 2013).…”
Section: Crude Fat (Ether Extract) and Fatty Acidsmentioning
confidence: 99%
“…There is a high variation in fatty acids profiles across insect species (Thompson, 1973;Lu et al, 1992). Womeni et al (2009) reported fatty acids of several edible insect species consumed in Cameroon to contain quantities of palmitic (8-38 %), oleic (9-48 %), linoleic (7-46 %) and α-linolenic acid (15-38 %) as percentage of oil content. Although the nutritional importance of linoleic and α-linolenic acid as essential amino acids is well recognized, the presence of high amounts of unsaturated fatty acids will also give rise to rapid oxidation of insect food products during processing, causing them to go rancid quickly (FAO, 2013).…”
Section: Crude Fat (Ether Extract) and Fatty Acidsmentioning
confidence: 99%
“…The nutritional quality of certain insects, their nymphs, and their larvae is also worth noting. Some species in particular are rich in ALA, like lepidoptera (Bombycidae, Saturniidae, and Noctuidae families) and orthoptera (Acrididae family) (Defoliart, 1991;Womeni et al, 2009). Imbrasia caterpillars, for example, or crickets contain 10% of ALA on dry matter.…”
Section: Climate: a Factor That Triggered Dietary Changesmentioning
confidence: 99%
“…the habitat in which the species lives and its diet) (Xiaoming et al 2010), as well as on the preparation process (boiling, frying, drying). In general, insects are an important source of fat (with a high content of polyunsaturated and essential fatty acids; Womeni et al 2009), protein (often rich of essential 2013), although their composition is highly variable across species and orders and also depending on the parts of the plant on which they feed (Bukkens 2005). Insects are often consumed as a whole, fried, sundried smoked, steamed in banana leaves (Uganda) or roasted in hot ash and sand (winged termites Hodotermes mossambicus in Botswana; Nonaka 1996), but they can also be processed into granular or paste forms.…”
Section: Invertebratesmentioning
confidence: 99%